Do oldest old individuals perceive receipt of informal care as a restriction or support of their autonomy?. (24th August 2022) - Zwar, Larissa; König, Hans-Helmut; van der Leeden, Carolin; Lühmann, Dagmar; Oey, Anke; Wiese, Birgitt; Weyerer, Siegfried; Werle, Jochen; Fuchs, Angela; Pentzek, Michael; Luppa, Melanie; Löbner, Margrit; et al.
Abstract: Objectives: Autonomy (defined as self-governance; not equivalent to independence) is relevant to well-being and psychological functioning. However, there is a lack of research on individuals aged >85 years and their perception of autonomy when receiving informal care. This study aims to answer the question if and how the receipt of informal care is associated with perceived autonomy of individuals aged over 85 years. Method: A cross-sectional study was conducted with data from follow-up 9 of the AgeQualiDe study (2015/2016), which is a multi-centric prospective cohort study in Germany. The analytical sample included 570 participants aged >85 years and with a score of ≥ 19 on the Mini-Mental-State-Examination. Perceived autonomy was assessed with the Perceived Autonomy in Old Age Scale. Receipt of care was assessed as performance of at least one care task (help with basic and instrumental activities of daily living, and supervision) by relatives or friends. Sociodemographic information, mental health, functional level and receipt of professional ambulatory care were controlled for. Results: Unadjusted and adjusted linear regression analyses indicated a significant negative association between receipt of informal care and perceived autonomy. The results remained stable in sensitivity analyses; no significant interaction effect was found for gender or education. Conclusion: Findings indicate that informal care recipients aged >85 years perceive lower autonomy compared to those not receiving care. Additional or other forms of support, and improving the care relationship and communication might be considered to support autonomy of care recipients aged >85 years.